Pengaruh Special Event “One Memorable Day With Oh Sehun” Terhadap Brand Image Skincare Whitelab (Survey Pada Pengunjung Special Event “One Memorable Day With Oh Sehun”) - Winda Krisnawati; Nani Nurani Muksin (Institut Nalanda, 2024)
One of the efforts made by the beauty company Whitelab to get consumers' attention is by attracting an actor from South Korea named Oh Sehun. The Whitelab company held a special event